Postulates on electromagnetic activity in biological systems and cancer - Pokorný, Jiří; Pokorný, Jan; Kobilková, Jitka (Integrative biology, 2013)
A framework of postulates is formulated to define the existence, nature, and function of a coherent state far from thermodynamic equilibrium in biological systems as an essential condition for the existence of life. This state is excited and sustained by energy supply. Mitochondria producing small packets of energy in the form of adenosine and guanosine triphosphate and strong static electric field around them form boundary elements between biochemical-genetic and physical processes. The transformation mechanism of chemical energy into useful work for biological needs and the excitation of the coherent state far from thermodynamic equilibrium are fundamental problems. The exceptional electrical polarity of biological objects and long-range interactions suggest a basic role of the endogenous electromagnetic field generated by living cells. The formulated postulates encompass generation, properties and function of the electromagnetic field connected with biological activity and its pathological deviations. Excited longitudinal polar oscillations in microtubules in eukaryotic cells generate the endogenous electromagnetic field. The metabolic activity of mitochondria connected with water ordering forms conditions for excitation. The electrodynamic field plays an important role in the establishment of coherence, directional transport, organization of morphological structures, interactions, information transfer, and brain activity. An overview of experimental results and physical models supporting the postulates is included. The existence of the endogenous biological electromagnetic field, its generation by microtubules and supporting effects produced by mitochondria have a reasonable experimental foundation. Cancer transformation is a pathological reduction of the coherent energy state far from thermodynamic equilibrium. Malignancy, i.e. local invasion and metastasis, is a direct consequence of mitochondrial dysfunction, disturbed microtubule polar oscillations and the generated electromagnetic field.
Keywords: mikrotubuly; Cell Transformation, Neoplastic; Mitochondria; elektromagnetická pole; Models, Biological; Electromagnetic Fields; Energy Metabolism; Humans; energetický metabolismus; Microtubules; lidé; mitochondrie; nádorová transformace buněk; biologické modely